Al-Kalimat Al-Minangkabauwiyah Dzatu Ashlin ‘Arabiy Fii Mu’jam Bahasa Indonesia-Minangkabau Harf “A” Ila “M” Namudzajan - Hifzi Candra (Mauriduna: Journal of Islamic Studies, 2020)
هدفت هذه الدراسة إلى اكتشاف الكلمات ذات أصل عربي في معجم Kamus Bahsasa Indonesia-Minangkabau من حرف A إلى M، وذلك بناء على أن بين اللغتين االمينانجكباوية والعربية علاقة قوية منذ دخول الإسلام في أرض مينانج؛ إذ الإسلام يحمل معه ثقافته ما لايوجد في اللغة المينانجكباوية، فاضطر المينانجيين الذين اعتنقوا الإسلام إلى أخذ بعض الألفاظ العربية لحاجة اتصالية ودينية وسياسية واقتصادية واجتماعية، وهدفت الدراسة إلى معرفة تغير نطق الكلمات العربية ومعناها بعد دخولها إلى اللغة المينانجكباوية، كما هدفت إلى محاولة الاستفادة منها في تعليم اللغة العربية للمينانجيين. واعتمد الباحث في إنجاز هذه الدراسة على المنهج الوصفي التحليلي الذي يصف وصفا دقيقا لموضوع الدراسة، وذلك من خلال المقارنة بين اللغتين اللغة العربية واللغة المينانجكباوية بالاعتماد على المعجم العربي و المعجم Kamus Bahasa Indonesia-Minangkabau ،ثم وصف تلك الكلمات وتحليلها، ووضع هذه الكلمات في نماذج عدة من الاستفادة في تعليم اللغة العربية للمينانجيين. The goal of the study is to reveal the borrowed minangkabau words from arabic in Kamus Bahasa Indonesia-minangkabau from letter A to letter M, it is considered based on the relationship between minangkabau and arabic is very closely since islam come to minangkabau land because Islam brings a culture that is not found in the Minangkabau land, so the people of Minangkabau are forced to absorb some of the foreign languages ( Arabic) to communicate, for religious,political, economic,and social needs. This study also intend to find out the changes in the pronunciation and meaning of words that occur in the words of borrowed Minangkabau derived from arabic, also trying to aplly it in teaching arabic for minangkabau.In this study, the researcher used an analytical description method that describes the subject of a proper study by comparing the two languages of the arabic and minangkabau language by referring to Arabic dictionary the minangkabau language dictinary, then describing and analyzing the words, researcher also trying to apply these words in teaching of Arabic for the people of Minangkabau.